Eliminating the Barriers to Employment Equity in the Canadian Workplace - Falkenberg, L. E. (Journal of business ethics, 1997)
Have employment equity programs achieved the goal of equity for women in the workplace? We argue that they have not because gender stereotypes still persist. In fact, they may have created resentment and antagonism towards successful women and employment equity initiatives. Arguments are developed for the Canadian government to create a self-regulating system, in which the government plays a role of educator as opposed to monitor.